The Sensitivity of Event Logs, Self-Administered Questionnaires and Photoplethysmography to Detect Treatment-Induced Changes in Female Sexual Arousal Disorder (FSAD) Diagnosis - Rellini, Alessandra (2006)
INTRODUCTION: The literature provides little evidence on what type of endpoints should be used to assess treatment-induced improvement in female sexual function. AIM: The main goal of this study was to provide empiric evidence on the sensitivity of different types of measures for detecting treatment-induced changes in female sexual dysfunction diagnosis. METHODS: The measures investigated in this study included event logs, self-administered questionnaires (Female Sexual Functioning Index; FSFI), vaginal photoplethysmography, and continuous subjective sexual arousal measured during exposure to erotic videos. Participants were 24 women with female sexual arousal disorder (FSAD) who received sex therapy, placebo, or gingko biloba in a four-arm double-blind placebo-controlled clinical trial. FSAD was diagnosed utilizing a semistructured interview administered at pre- and post-treatment. Those women who did not meet FSAD criteria at post-treatment (N = 10) were labeled as “improved,” while women who still met FSAD criteria (N = 14) were categorized as “not improved” even if they showed signs of improvements. MAIN OUTCOME MEASURE: Change scores from pre- to post-treatment on the FSFI, event logs, vaginal photoplethysmography, and continuous subjective levels of sexual arousal were used to predict whether women improved at post-treatment. Results were checked with exact logistic regression to control for the small sample size. RESULTS: The FSFI was the only measure to significantly predict whether women improved at post-treatment. The findings from this study lend support for the use of validated questionnaires as endpoint criteria in detecting treatment-induced changes in women’s sexual dysfunction.